PENINGKATAN KOMPETENSI GURU DALAM MENGGUNAKAN MEDIA PEMBELAJARAN MELALUI SUPERVISI AKADEMIK DI SMAN 1 KERUMUTAN KABUPATEN PELALAWAN PROVINSI RIAU TAHUN PELAJARAN 2022/2023 - MISNARTI MISNARTI (JURNAL ILMIAH MAKSITEK, 2022)
The problem in this study is that there are still many teachers who have not designed lesson plans in accordance with the Permendiknas, there are teachers who have not included the learning methods and strategies used, the selection of media is not appropriate. The purpose of this study was to obtain an increase in teacher competence in using learning media at SMAN 1 Kerumutan, Pelalawan Regency. The type of research used in this research is the school action research method (PTS). Location The research was conducted at SMAN 1 Kerumutan. Time The research was carried out in semester I July December 2022/202 Academic Year. The subjects of the school action research were 30 teachers at SMAN 1 Kerumutan. The technique of collecting data from this school action research is through quantitative data obtained from observation and interviews. The data analysis technique used in this study is quantitative data analysis originating from the acquisition of the instrument. The results of the study show that based on the results of the research discussed in the previous section, it can be concluded that there is an increase in teacher competence in the use of instructional media through academic supervision at SMAN 1 Kerumutan, Riau Province, with a score in the first cycle of 51%, an increase in the second cycle of 92%.